Fracture resistance of bleached teeth restored with different procedures - Bandeca, Matheus Coelho [UNESP]; Pinto, Shelon Cristina Souza [UNESP]; Calixto, Luiz Rafael [UNESP]; Saad, José Roberto Cury [UNESP]; Barros, Érico Luiz Damasceno; El-Mowafy, Omar; Porto Neto, Sizenando de Toledo [UNESP] (ABM, ABC, ABPol, 2012)
This study evaluated the fracture resistance of teeth submitted to internal bleaching and restored with different non-metallic post. Eighty mandibular incisors were endodontically treated and randomly divided in 10 groups (n = 8): G1- restored with composite resin (CR), G2- CR + fiber-reinforced composite post (FRC, Everstick post, Sticktech) cemented with resin cement self-etch adhesive (RCS, Panavia F 2.0, Kuraray), G3- CR + FRC + self-adhesive resin cement (SRC, Breeze, Pentral Clinical), G4- CR+ glass fiber post (GF, Exacto Post, Angelus) + RCS, G5- CR + GF + SRC. The G6 to G10 were bleached with hydrogen peroxide (HP) and restored with the same restorative procedures used for G1 to G5, respectively. After 7 days storage in artificial saliva, the specimens were submitted to the compressive strength test (N) at 0.5 mm/min cross-head speed and the failure pattern was identified as either reparable (failure showed until 2 mm below the cement-enamel junction) or irreparable (the failure showed <2 mm or more below the cement-enamel). Data were analyzed by ANOVA and Tukey test (α = 0.05). No significant difference (p < 0.05) was found among G1 to G10. The results suggest that intracoronal bleaching did not significantly weaken the teeth and the failure patterns were predominately reparable for all groups. The non-metallic posts in these teeth did not improve fracture resistance.
Keywords: dental bleaching; fracture resistance; fiber posts; composite resin